PENGARUH LEVERAGE, PROFITABILITAS, FREE CASH FLOW, DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2013-2017) - Luqmana Chakim, 15.05.52.0010; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of Leverage, Profitability, Free Cash Flow and Managerial Ownership on Profit Management in manufacturing sector companies. This research was conducted on the Indonesia Stock Exchange (IDX) in 2013-2017.The sample in this study was taken using a purposive sampling method with 205 companies. The data used is secondary data in the form of company financial statements which are analyzed using Multiple Regression Analysis. The results of the analysis show that leverage has a significant negative effect on earnings management, profitability does not affect earnings management, whereas Free Cash Flow and managerial ownership have a significant positive effect on earnings management.